Component Analysis of Purification System of RSG-GAS - Mike Susmikanti; Entin Hartini; Aep Saepudin; Jos Budi Sulistyo (Jurnal Pengembangan Energi Nuklir, 2018)
COMPONENT ANALYSIS OF PURIFICATION SYSTEM OF RSG-GAS. Component reliability analysis is required in the aging management of RSG-GAS that has reached an age of 30 years. One of the required analyses is the assessment of the distribution of repair data and the estimation of related parameters. The Primary Purification System (KBE01) and the Purification and Warm Water Layer System (KBE02) are important components of RSG-GAS. By knowing the repair data distribution, the parameters of the most frequently occurring component repair and the average of the repair period can be estimated, so that the required provision of spare parts for the smooth operation of the reactor can be predicted. The purpose of this study is to analyze the components of the KBE01 and KBE02 systems through the data distribution approach using the matching test method. With the matching test, the form of data distribution can be determined, so the parameter of the average component repair period that can be used as a comparison of the maintenance period of the components can be estimated. The repair times of KBE01 and KBE02 in RSG-GAS on Core 52 through Core 88 (2006-2015) were analyzed using goodness-of-fit test. The repair times of AA068 and AP001 KBE01 follow the exponential distribution with average repair times of 631.6 and 451.2 days, respectively. The repair times of WWL and AA002 KBE02 followed an exponential distribution with average repair times of 239.5 days and 888.0 days.